Thermodynamic properties of supercritical carbon dioxide using molecular dynamics simulation - Chenyang Sun; Chaofeng Hou; Lin Chen; Wenke Zhao; Yaning Zhang (Next Energy)
Supercritical carbon dioxide (scCO2) is widely used in various industrial and energy systems, exerting profound influences on the operational efficiencies of these devices through changing their physical properties. Molecular dynamics (MD) simulation is a powerful tool to calculate the thermodynamic properties and larger simulation scales are essential for scCO2 characterized by significant local inhomogeneities. In this study, large-scale MD simulation was used to obtain the thermodynamics properties including density, isobaric heat capacity, isochoric heat capacity, volume expansion coefficient, isothermal compression coefficient, and Joule–Thomson coefficient of scCO2 at temperatures of 300–900 K and pressures of 7.3773–20 MPa, with average relative errors of 3.76%, 3.93%, 3.11%, 5.76%, 7.07%, and 14.24%, respectively. The corresponding Widom lines of these thermodynamic properties were obtained, and they formed an approximately fan-shaped area called “Widom line region.” The expressions of the Widom lines were fitted with R2 of above 97.48%, well guiding the operation of scCO2 systems.